Quantifying the Relative Importance of Phylogeny and Environmental Preferences As Drivers of Gene Content in Prokaryotic Microorganisms - Tamames, Javier; Sánchez, Pablo D.; Nikel, Pablo I.; Pedrós-Alió, Carlos (Frontiers in Microbiology, 2016)
Two complementary forces shape microbial genomes: vertical inheritance of genes by phylogenetic descent, and acquisition of new genes related to adaptation to particular habitats and lifestyles. Quantification of the relative importance of each driving force proved difficult. We determined the contribution of each factor, and identified particular genes or biochemical/cellular processes linked to environmental preferences (i.e., propensity of a taxon to live in particular habitats). Three types of data were confronted: [i] complete genomes, which provide gene content of different taxa; [ii] phylogenetic information, via alignment of 16S rRNA sequences, which allowed determination of the distance between taxa, and [iii] distribution of species in environments via 16S rRNA sampling experiments, reflecting environmental preferences of different taxa. The combination of these three datasets made it possible to describe and quantify the relationships among them. We found that, although phylogenetic descent was responsible for shaping most genomes, a discernible part of the latter was correlated to environmental adaptations. Particular families of genes were identified as environmental markers, as supported by direct studies such as metagenomic sequencing. These genes are likely important for adaptation of bacteria to particular conditions or habitats, such as carbohydrate or glycan metabolism genes being linked to host-associated environments.